TRIPUHYITE, FESBO4, REVISITED - Berlepsch P.; Armbruster T.; Brugger J.; Criddle A.J.; Graeser S. (My University, 2003)
The exact nature of tripuhyite remains controversial more than 100 years after the first description of the mineral. Different stoichiometries and crystal structures (rutile or tri-rutile types) have been suggested for this Fe-Sb-oxide. To address these uncertainties, we studied tripuhyite from Tripuhy, Minas Gerais, Brazil (type material) and Falotta, Grisons, Switzerland using single-crystal and powder X-ray diffraction (XRD), optical microscopy and electron microprobe analysis. Electron microprobe analyses showed the Fe/Sb ratios to be close to one in tripuhyite from both localities. Single crystal XRD studies revealed that tripuhyite from the type locality and from Falotta have the rutile structure ( P 4 2 mnm, a = 4.625(4) c = 3.059(5) and a = 4.6433(10) c = 3.0815(9) Å, respectively). Despite careful examination, no evidence for a tripled c parameter, characteristic of the tri-rutile structure, was found and hence the structure was refined with the rutile model and complete Fe-Sb disorder over the cationic sites in both cases (type material: R 1 = 3.61%; Falotta material: R 1 = 3.96%). The specular reflectance values of type material tripuhyite and lewisite were measured and the following refractive indices calculated (after Koenigsberger): tripuhyite n min = 2.14, n max = 2.27; lewisite (cubic) n = 2.04. These results, together with those of ⁵⁷ Fe and ¹²¹ Sb Mössbauer spectroscopy on natural and synthetic tripuhyites reported in the literature, indicate that the chemical formula of tripuhyite is Fe ³⁺ Sb ⁵⁺ O 4 (FeSbO 4 ). Thus, tripuhyite can no longer be attributed to the tapiolite group of minerals of general type AB 2 O 6 . A comparison of the results presented with the mineralogical data of squawcreekite suggests that tripuhyite and squawcreekite are identical. In consequence, tripuhyite was redefined as Fe ³⁺ Sb ⁵⁺ O 4 with a rutile-type structure. Both the proposed new formula and unit cell (rutile-type) of tripuhyite as well as the discreditation of squawcreekite have been approved by the Commission on New Mineral and Mineral Names (CNMMN) of the International Mineralogical Association (IMA).
Keywords: Tripuhyite